Strengthening teacher professional programs: Insights from Scopus AI - H. Husamah; Jalilah Azizah; Tutut Indria Permana; Yanur Setyaningrum (Jurnal Pendidikan Profesi Guru, 2025)
The quality of education in Indonesia depends heavily on the competence and capabilities of educators. Although various initiatives have been implemented to enhance teacher professional development, significant challenges persist. This article aims to critically review the various initiatives implemented in Indonesia, assessing their strengths and weaknesses, and comparing them with best practices from other countries. Using data from Scopus AI, the study analyzes the effectiveness and potential of these programs. Through natural language and keyword searches, this article identifies key challenges faced by teacher professional programs, including the misalignment between policy and practice, low participation in online sessions, and limited technological infrastructure. Additionally, this article presents a concept map illustrating the key components of teacher professional development programs in Indonesia. In conclusion, strengthening policies, increasing teacher participation, and optimizing technology in training can strengthen professional development programs and improve the overall quality of education in Indonesia. Further research is needed to explore the long-term impacts of integrating technology into teacher professional development programs, especially in areas with limited digital infrastructure.